Konsep Diri Siswa SMP Santo Aloysius Turi Yogyakarta yang Tinggal di Asrama di Tinjau dari Kondisi Keluarga Kandung - Veronika Iki; M.M Sri Hastuti (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to describe and determine the level of self-concept among junior high school students at Santo Aloysius Turi Yogyakarta who live in dormitories, viewed from the perspective of their biological family conditions.The research subjects were junior high school students at Santo Aloysius Turi who live in dormitories. They numbered 68 students, consisting of 39 male students and 29 female students. This research used a descriptive quantitative method. Data collection in this study used a self-concept questionnaire for junior high school students at Santo Aloysius Turi Yogyakarta who live in dormitories, viewed from the perspective of their Biological Family Conditions, containing 96 items. The questionnaire was structured using aspects of self-concept according to Burn (1993). The reliability of the questionnaire was tested using the Cronbach's Alpha (α) approach, with a resulting coefficient value of 0.917. The number of valid items was 70. The data analysis technique used descriptive statistics with categorizations of very good, good, average, poor, and very poor.The research results show that most junior high school students at Santo Aloysius Turi who live in dormitories have self-concepts as follows: (1) 16 students have very high self-concept (23.5%). (2) 27 students (39.7%) have high self-concept. (3) 23 students (33.8%) fall into the average self-concept category. (4) 2 students (3%) have low self-concept, and there are no students (0%) who have very low self-concept.